Applying the Analytic Hierarchy Process (AHP) to Accessible Housing: A Multi-Disability Perspective - VALDERRAMA ULLOA, CLAUDIA ALEJANDRA; FERRADA CALVO, XIMENA VERÓNICA; Felipe Herrera (MDPI AG, 2025)
Accessible housing plays a vital role in promoting independent living and quality of life for people with disabilities. However, the existing design standards often fail to address the specific needs of diverse disability groups. This study aims to establish architectural and habitability criteria for housing adapted to various disabilities, including wheelchair users, individuals with achondroplasia (little people), Autism Spectrum Disorder (ASD) and Down syndrome, individuals with visual and hearing impairments, and older adults, by integrating international frameworks and prior research. The Analytic Hierarchy Process (AHP) was used to prioritize key factors in the housing design. The factors analyzed included autonomy, independence, safety, comfort, communication, and mobility. Findings reveal that autonomy consistently emerged as the most relevant criterion across groups, particularly for older adults (61.8%), wheelchair users (83%) and little people (64%). Secondary priorities varied: mobility was emphasized by wheelchair users (77%), communication by visually impaired individuals (64%), and comfort by deaf and hard of hearing participants (43%). The results underscore the need for housing solutions that reflect the priorities of each disability group. This study contributes by validating user-centered design criteria and offering a framework to guide inclusive housing policies and practices. By highlighting needs, it bridges the gap between generic accessibility standards and design. These findings support policy development and enrich the literature by incorporating unique resident-centered perspectives and overlooked indicators of housing accessibility and inclusive residential design.